Tinjauan Sosiologi Sastra Karya Taufiq Ismail dalam Puisi: Syair Orang Lapar - Falah Arifbilah Subagiyo; Akhmad Fatoni (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
Literary work always contains the author's view of reality as a social institution created by an author. Issues that are often strung together become a view or criticism of life. It certainly describes social life as a reality that occurs in an environment. One type of literary work that contains a view of reality is his poem Taufiq Ismail entitled " Syair Orang Lapar ". The purpose of this research is to find out the meaning of social impact in Taufiq Ismail's poem entitled "Syair Orang Lapar". The poem contains the effects that occur when a situation befall on humans. It is hoped that this study can make us more sensitive to conditions and conditions. The reason for choosing Taufiq Ismail's poetry is because the language is straightforward and concrete. With poetry that is straightforward and concrete, meaning can be sharp and comprehensive. The poem is analyzed on aspects of social impact that occur in a phenomenon. The methods used in this research is qualitative using a sociological approach. The technique used is descriptive analysis technique. Researchers position themselves as a single instrument. The process is through noting things that are related to aspects of social impact as material for analysis and sources of understanding. The results of this study indicate that the poem entitled " Syair Orang Lapar " illustrates three impacts of social reality in society, namely: 1) not ready to face drought, 2) the lack of means of expressing freedom, and 3) the consequences of natural disasters. Based on these conclusions, the researcher draws a common thread that natural disasters cannot be avoided but as humans can prepare themselves to face disasters in terms of their social.